2021
DOI: 10.1002/mdc3.13396
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Apathy across Different Variants of Progressive Supranuclear Palsy

Abstract: BackgroundBackground: Apathy and depression commonly occur in patients with progressive supranuclear palsy (PSP)-Richardson's syndrome variant; depression often requiring treatment. Little is known, however, about apathy and depression among other PSP variants. Methods Methods: We prospectively studied 97 newly diagnosed PSP patients. All were classified into a PSP variant using the 2017 Movement Disorder Society-PSP criteria and administered the Geriatric Depression and Apathy Evaluation Scales. Differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In about 40-80% of patients, parkinsonism starts asymmetrically, 50% of patients present with tremor, and about 50-70% of patients have moderate to good response to levodopa early in the disease course (169,172). While some studies found no difference in apathy or depression between PSP-P and RS (76,173), apathy was more frequent in PSP-P in one study (75) and in PSP-R in another (174), but further studies are needed. Early cognitive decline is more common in RS than PSP-P (76,172) and generally, neuropsychiatric and cognitive symptoms are more severe in both PSP variants compared to PD (76).…”
Section: Clinical Syndromes With Less Association To a Primary Tauopa...mentioning
confidence: 98%
“…In about 40-80% of patients, parkinsonism starts asymmetrically, 50% of patients present with tremor, and about 50-70% of patients have moderate to good response to levodopa early in the disease course (169,172). While some studies found no difference in apathy or depression between PSP-P and RS (76,173), apathy was more frequent in PSP-P in one study (75) and in PSP-R in another (174), but further studies are needed. Early cognitive decline is more common in RS than PSP-P (76,172) and generally, neuropsychiatric and cognitive symptoms are more severe in both PSP variants compared to PD (76).…”
Section: Clinical Syndromes With Less Association To a Primary Tauopa...mentioning
confidence: 98%
“…Patients with PSP frequently experience depression [3][4][5][6]14,15 and are commonly prescribed antidepressants. 14,15 In this case, depres- PSP and corticobasal syndrome, selective serotonin reuptake inhibitors may be used; however, tricyclic antidepressants should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PSP frequently experience depression [3][4][5][6]14,15 and are commonly prescribed antidepressants. 14,15 In this case, depres- PSP and corticobasal syndrome, selective serotonin reuptake inhibitors may be used; however, tricyclic antidepressants should be avoided. 16 Nevertheless, in a study of 892 patients with PSP, 231 (26%), 60 (7%), and 114 (13%) patients were prescribed selective serotonin reuptake inhibitors/serotonin-noradrenaline reuptake inhibitors, tricyclic antidepressants, and other antidepressants, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The cortical variants of PSP show worse motor disability, cognitive impairment and activities of daily living compared with subcortical variants of PSP [31,33 ▪ ]. Depression is observed across PSP variants, except in PSP-speech/language [34]. The absence of ocular motor impairments was a predictor of long (≥10 years) survival, while early frontal lobe dysfunction predicted shorter survival, in PSP in another study, with PSP-parkinsonism particularly frequent in the long survival group [35 ▪ ].…”
Section: Understanding Clinical and Anatomical Heterogeneitymentioning
confidence: 92%